GeneDesign: Rapid, automated design of multikilobase synthetic genes - Richardson, Sarah M.; Wheelan, Sarah J.; Yarrington, Robert M.; Boeke, Jef D.

(untitled) (Genome Research, 2006)
Modern molecular biology has brought many new tools to the geneticist as well as an exponentially expanding database of genomes and new genes for study. Of particular use in the analysis of these genes is the synthetic gene, a nucleotide sequence designed to the specifications of the investigator. Typically, synthetic genes encode the same product as the gene of interest, but the synthetic nucleotide sequence for that protein may contain modifications affecting expression or base composition. Other desirable changes typically involve the revision of restriction sites. Designing synthetic genes by hand is a time-consuming and error-prone process that may involve several computer programs. We have developed a tools environment that combines many modules to provide a platform for rapid synthetic gene design for multikilobase sequences. We have used GeneDesign to successfully design a synthetic Ty1 element and a large variety of other synthetic sequences. GeneDesign has been implemented as a publicly accessible Web-based resource and can be found at http://slam.bs.jhmi.edu/gd.